2019
DOI: 10.1111/anu.12901
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different dietary copper sources on the growth and intestinal microbial communities of Pacific white shrimp ( Litopenaeus vannamei )

Abstract: An 8‐week feeding trial was conducted to evaluate the effects of dietary copper sources on growth performance and intestinal microbial communities of juvenile Pacific white shrimp (Litopenaeus vannamei). Four isonitrogenous (420 g/kg crude protein) and isolipidic (70 g/kg crude lipid) experimental diets were formulated to contain different copper sources, Diet NSC (no‐supplemented copper), Diet CS (copper sulphate), Diet Availa (copper amino acid complex from Availa®Cu100) and Diet M (1:1, copper sulphate + co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 100 publications
0
6
0
Order By: Relevance
“…Mohammady et al (2021) attributed the upregulation of these genes to the continuous and slow release of Zn from ZnO-K as compared with other Zn forms. Pacific white shrimp Litopenaeus vannamei that were fed a diet supplemented with Cu-amino acid complex (Availa Cu) showed a higher expression of Cu/Zn SOD, ALP, ACP, and LZM genes in the hepatopancreas than shrimp that were fed a CuSO 4 -supplemented diet (Yuan et al 2019a(Yuan et al , 2019b. Similarly, organic Zn (Availa Zn) and a combination of organic and inorganic Zn resulted in higher upregulation of Cu/Zn SOD, ALP, ACP, and LZM gene expression levels in the shrimp hepatopancreas than inorganic Zn (Yuan et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mohammady et al (2021) attributed the upregulation of these genes to the continuous and slow release of Zn from ZnO-K as compared with other Zn forms. Pacific white shrimp Litopenaeus vannamei that were fed a diet supplemented with Cu-amino acid complex (Availa Cu) showed a higher expression of Cu/Zn SOD, ALP, ACP, and LZM genes in the hepatopancreas than shrimp that were fed a CuSO 4 -supplemented diet (Yuan et al 2019a(Yuan et al , 2019b. Similarly, organic Zn (Availa Zn) and a combination of organic and inorganic Zn resulted in higher upregulation of Cu/Zn SOD, ALP, ACP, and LZM gene expression levels in the shrimp hepatopancreas than inorganic Zn (Yuan et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In our feeding trial, dietary MAACs reduced the pathogenic bacterial load ( Streptococcus and Staphylococcus ) and enhanced the colonization of beneficial bacteria ( Bacillus and Lactobacillus ) in the intestine of Nile Tilapia (El‐Sayed et al 2023). Beneficial bacteria can convert parts of the food that they ingest into microbial biomass, which can be utilized by the animal host (Yuan et al 2019a, 2019b). This process can prevent pathogenic bacteria from colonizing the fish gut and in turn promotes the immunological, antioxidant, and metabolic status of the host fish (Ringø et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Proteobacteria was dominant in gut of fish and shrimp. The Vibrio was the largest proportion of Proteobacteria and a potential pathogen in intestine of Litopenaeus vannamei , which led to vibriosis outbreaks in shrimp (Yuan et al, 2019). The genus of Fusibacter could generate sulphide from elemental sulphur or thiosulphate (Hania et al, 2012), which may result in a rapid and high mortality in animals (Bagarinao & Lantin‐Olaguer, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the composition of the dominant intestinal microbiota of L. vannamei was also significantly affected by the diet containing fresh BSFL. Previous studies showed that the intestinal microbiota of L. vannamei was dominated by Proteobacteria and Bacteroidetes, which constitute the core flora, regardless of the diet administered (Yuan et al, 2019). However, chronic intestinal microecological disorders or intestinal inflammation was often caused by the excessive relative abundance of Proteobacteria (Mukhopadhya et al, 2012;Shin et al, 2015).…”
Section: Microbiota Analysis Of Shrimp Intestinementioning
confidence: 98%
“…T h e P C R amplification was performed in a total volume of 50 mL containing 25 mL of KOD FX Neo Buf (2×), 10 mL of 2 mM dNTP, 1 mL of KOD FX Neo (TOYOBO), 2.5 mL of 10 mM each primer, and 60 ng of DNA template, and finally, ddH 2 O was added to 50 mL. PCR amplification was performed on the PCR system under the following conditions: (a) 1*(3 min at 95°C), (b) 25*(30 s at 95°C; 30 s at 55°C; 1 min at 72°C), and (c) 10 min at 72°C, 10°C until halted by the user (Yuan et al, 2019).…”
Section: F (5′-agrgtttgatyntggctcag-3′) and 1492r (5′-t A S G G H T A...mentioning
confidence: 99%